STUDY OF LEVELS OF SERUM CREATINE PHOSPHOKINASE AND LIVER ENZYMES AS A PROGNOSTIC INDICATORS IN ACUTE ORGANOPHOSPHORUS POISONING - Kollur, Banashankari S; Mulimani, Mallanna S (International Journal of Clinical and Biomedical Research, 2018)
Background: Organophosphorus (OP) poisoning is one of the most common poisoning in rural and in developing country. Due to their easy availability and cost effective it is used frequently for homicidal and suicidal attempts. Routinely used biochemical markers like Erythrocyte cholinesterase (EChE) and Plasma cholinesterase (PChE) are used for the diagnosis of acute organophosphorus (OP) poisoning but estimation of these are very costly and not easily available. The mortality increases with increase in initial creatine phosphokinase level and can be used as alternative biomarker. Hence study was done to estimate levels of serum Creatine Phosphokinase (CPK) and liver enzymes in acute OP poisoning patients and its prognostic significance. Methodology: Patients (80) admitted in our hospital were included in this study. A brief history and detailed clinical examination was performed and patients were categorized on the basis Modified Dreisbach's clinical criteria classification. Serum levels of Creatine kinase (CK) and Liver enzymes were analysed at the time of admission. The outcome of the patients were observed. Results: Out of 80 patients recruited for the study, 41 cases (51.3%) were females, and 39 cases (48.8%) were males. Majority of them were in the age group of 21-30 years. More cases of OP poisoning were among agriculturalists 28 (35%) and housewife 21 (28.8%) and among students 15 (18.8%). Malathion was the most common compound used followed by Monocrotphos. 60% had mild, 31.3% had moderate and 8.8% had severe poisoning. There is increase in Creatine Phosphokinase (CPK) levels in 6 patients who survived with ventilator support and also in 2 patients who died with ventilator support which was statistically highly significant (p<0.05). Serum liver enzymes were within normal limits. Conclusion: Elevated Creatine kinase is commonly seen in OPC poisoning. High initial serum Creatine Phosphokinase (CPK) levels are associated with severe degree of poisoning and are associated with complications and mortality. Serum liver enzymes (SGOT AND SGPT) are not elevated in OP poisoning.